(3TQM efJgi GdhUhd hGdCed aj Ydei GdCUhd hGdLOds - (3fXGe GdOjf GdMSf Hf eMeO Hf GdMSjf GdfjSCHhQis; (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS, CHh YeQh LeGd GdOjf GHf GdMGLH,J (B646 (3g` s
(3ChdgG (B:s
(3bGd GdeMbb GdYdGeI fXGe GdOjf GdfjSGHhQi (B: (3GdJLejO GdcGed Ydi EMSGfg GdTGed ESJMb ef Mb dg hLhH GdhLhO hHYO aEf CabQ Ndb Gddg Edi ZaQGfg GdMSf Hf eMeO GdfjSGHhQi jbhd ef GdeYdhe Cf GdYdhe JJHGjf ai GdaVd s
(3BNQgG (B:s
(3fLR GdcJGH hddg GdMeO ChdkG hBNQkG Gddge GZaQ deDdag hcGJHg hbGQFI hdSGFQ GdeSdejf CLeYjf Efc Ydi cd TF bOjQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3NWJ ajg YHGQGJ GdeJf (B" (3efJgi GdhUhd (B" (3dGHf GdMGLH HGdMeQIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3CUhd Gdabgs